2022
DOI: 10.3389/fpubh.2022.858370
|View full text |Cite
|
Sign up to set email alerts
|

Development and Feasibility of an Online Brief Emotion Regulation Training (BERT) Program for Emerging Adults

Abstract: Mental wellness is a critical component of healthy development in emerging adulthood and serves to protect against stress and promote resilience against psychopathology. Emotion regulation is a key mechanism for effective prevention because of its role in socio-emotional competence and its transdiagnostic significance for psychopathology. In this feasibility study, a brief, time and cost-effective emotion regulation training program for emerging adults (BERT) was developed and tested using the RE-AIM framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 79 publications
1
21
0
Order By: Relevance
“…The more emerging adults will be able to identify and regulate their emotions, the more they will probably be able to concentrate, feel accepting of themselves, and feel autonomous, fulfilled, and oriented in their life. The results of the current study are consistent with the study by Guassi Moreira et al (2022), which showed that emerging adults felt more fulfilled when they sensed that they could regulate their emotions. The results of our study on emotional regulation and well-being thus align with American studies, suggesting that the interventions that we will suggest could potentially be extended to emerging adults in other locations around the world.…”
Section: Predictors Of Psychological Well-beingsupporting
confidence: 93%
“…The more emerging adults will be able to identify and regulate their emotions, the more they will probably be able to concentrate, feel accepting of themselves, and feel autonomous, fulfilled, and oriented in their life. The results of the current study are consistent with the study by Guassi Moreira et al (2022), which showed that emerging adults felt more fulfilled when they sensed that they could regulate their emotions. The results of our study on emotional regulation and well-being thus align with American studies, suggesting that the interventions that we will suggest could potentially be extended to emerging adults in other locations around the world.…”
Section: Predictors Of Psychological Well-beingsupporting
confidence: 93%
“…In addition, there may be an overload of counseling center capacity to meet student mental health needs (Xiao et al, 2017). To address these challenges, universities/colleges can (and do) consider offering services that are supplemental to traditional mental health service, including brief online or course-based emotion regulation training (Gatto et al, 2022;Van Doren et al, 2021), mindfulness-based interventions (Jia-Yuan et al, 2022), and stress reduction programs that may help disrupt the developmental cascade between ACEs and emerging mental health problems (Kalmakis et al, 2020;Karatekin, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…14 The method was adapted to a virtual setting to refine the content of an online brief emotion regulation training program for emerging adults. 15 The authors indicated that the virtual brainwriting premortem provided invaluable input, simplified scheduling, and data collection.…”
Section: Brainwriting Premortem Methodsmentioning
confidence: 99%
“…Additional case studies in healthcare include a project in rural India to increase access to healthcare 13 and a US program to design an electronic health record‐based discharge readiness communication tool 14 . The method was adapted to a virtual setting to refine the content of an online brief emotion regulation training program for emerging adults 15 . The authors indicated that the virtual brainwriting premortem provided invaluable input, simplified scheduling, and data collection.…”
Section: Brainwriting Premortem Methodsmentioning
confidence: 99%